Global and LMIC insights into Acceptance and Commitment Therapy (ACT) : A bibliometric study from 1998 to 2023 - Lim, Re Gal; Voon, Siok Ping; Fatahyah, Yahya; Fitri Suraya, Mohamad; Aidi, Ahmi (Elsevier B.V., 2024)
This bibliometric study examined the current state, publication trends, key authors and counties, inter-country collaboration, and research themes of the Acceptance and Commitment Therapy (ACT) publications produced globally and in low-to-middle-income countries (LMIC) from 1998 to 2023. 1458 ACT publications, with 287 (19.68%) publications from LMIC, were extracted from the Scopus database and analyzed using biblioMagika, OpenRefine, VOSviewer, and Biblioshiny. The global publications received 41,357 citations over 25 years, while the LMIC publications received approximately 4% (n = 1,713) of the total citations since its first publication in 2010. Most ACT publications were written in English (92.80%) and focused on the fields of psychology and medicine. Publication output rose over time, yet citation trends varied globally and in LMIC. Michael Twohig was the most prolific author with 71 publications, whereas Steven Hayes was the most highly cited author with 6,115 total citations. The US, UK, Iran, and China were the most productive contributors in the global and LMIC contexts, accounting for 51.9% (n = 757) and 76.3% (n = 219) of total publications, respectively. Additionally, the US was the central hub of international scholarly collaboration while limited inter-country collaboration existed in some parts of Asia and Europe. Co-word and factorial analyses identified thematic clusters, knowledge evolution, and potential research opportunities for ACT scholars.